Pelatihan Public Speaking: Pembekalan Kompetensi Siswa-Siswi SMK Negeri 2 Kabupaten Tangerang - Serius Zebua; Lianah The; Agus Kusnawan; Andy Andy; Eso Hernawan; Tri Angreni; Georgius Listen (Jurnal Pengabdian Masyarakat, 2025)
This community service activity was carried out with the aim of improving the public speaking skills of students of SMK Negeri 2 Sepatan, Tangerang, especially the Department of Accounting and Institutional Finance. The background of this activity departs from the problem of low confidence and oral communication skills of students which has an impact on their limitations in conveying ideas, making presentations, and facing job interviews. The implementation method uses a socialization, simulation, and hands-on approach for three hours, focusing on mastering basic communication concepts, techniques for overcoming nervousness, and effective messaging strategies. Participants in the activity as many as 152 students showed active involvement throughout the training process. The results of the activity showed an increase in students' courage to speak in public, the ability to use clear intonation, and the preparation of a more coherent message structure. In addition, students also show higher motivation to develop communication skills as a provision to face the world of work. From the partner side, the school appreciates this activity because it supports the development of soft skills that are rarely given in the formal curriculum. Overall, this service activity has been proven to have a positive impact on both students and schools, and can be replicated in other educational institutions to strengthen the work readiness of the younger generation.